1995
DOI: 10.1128/aac.39.4.834
|View full text |Cite
|
Sign up to set email alerts
|

Tolerability, kinetics, and efficacy of subconjunctival pefloxacin in pigmented rabbits

Abstract: Pefloxacin has been shown to have good intraocular penetration when given systemically. In order to extend its clinical use, we have assessed the tolerability, kinetics, and efficacy of subconjunctival pefloxacin in phakic pigmented rabbits. The tolerability of a single subconjunctival injection of pefloxacin (0.8, 1.6, 8, or 16 mg in 0.2 ml) in the right eyes of eight rabbits was evaluated by clinical and histopathological examination. The 0.8-mg dose of pefloxacin was well tolerated. The kinetics was evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…2,27 The corneal AUCs in this study are comparable to the scleral AUCs on a per gram basis. The corneal levels after periocular administration could be due to a leak back along the needle tract from the site of injection, diffusion across conjunctiva into tear fluid, or the presence of a direct penetration pathway from the subconjunctival space into the aqueous FIGURE 3.…”
Section: Discussionmentioning
confidence: 50%
“…2,27 The corneal AUCs in this study are comparable to the scleral AUCs on a per gram basis. The corneal levels after periocular administration could be due to a leak back along the needle tract from the site of injection, diffusion across conjunctiva into tear fluid, or the presence of a direct penetration pathway from the subconjunctival space into the aqueous FIGURE 3.…”
Section: Discussionmentioning
confidence: 50%
“…The low permeant concentration at the back of the eye after subconjunctival injection observed in the current study is also consistent with previous findings. For example, previous studies have reported that subconjunctival injections of aztreonam (23), ceftriaxone (24), pefloxacin (25), ciprofloxacin (26), cyclosporine (27), cefazolin, and cefamandole (28) can achieve only low concentrations of these compounds in the vitreous. In all cases, drug concentrations in the vitreous were found to be less than 0.05% of those in the injection solutions over the durations of these studies.…”
Section: Absorption Barriers Of Subconjunctival Injectionmentioning
confidence: 97%
“…Pefloxacin is well distributed to the tissues [ V d(area)  = 2.36 ± L/kg and V ss  = 1.54 ± 0.33 L/kg, respectively]. The elimination half-life of pefloxacin after IV administration ( t ½β  = 8.44 ± 0.48 h) was much longer than those previously reported in other studies: 2.21 h in calves (10), 1.12–1.6 h in goats (12, 13), and 2.84–3.25 in ducks (18) but comparable to that reported in sheep ( t ½β  = 6.88 h) (16). …”
Section: Discussionmentioning
confidence: 86%
“…In poultry medicine, the potential usefulness of pefloxacin for treatment of common infections in chickens for fattening requires detailed information on pharmacokinetics properties to establish the orally administered dose necessary for maintaining bactericidal drug concentrations in the body. Although studies on the kinetic behavior of pefloxacin in many species including man ( 8 10 ), calves ( 11 ), rabbits ( 12 ), goats ( 13 , 14 ), pigs ( 15 ), and sheep ( 16 ) are available; pharmacokinetic investigations on pefloxacin in poultry are limited ( 17 , 18 ). Results of a preliminary study in our laboratory in chickens were presented as a poster at 9th International EAVPT Congress ( 19 ).…”
Section: Introductionmentioning
confidence: 99%